"Environmental Issues in the Sustainable Development of the Republic of Uzbekistan: Dolzarb Ecological Problems and Their Legal Solutions (Eurasian Journal of Research, Development and Innovation, 2022)
One of the environmental principles in Article 4 of the Law on Nature Protection is "harmonization of national, interregional and international interests in the field of nature protection". Because processes and events occurring in nature, different from those in society, know neither administrative nor natural boundaries. Pollution of the Syr Darya tributaries by radioactive substances in Kyrgyzstan will undoubtedly have a negative impact on the environment in the republics of Uzbekistan and Kazakhstan. The ecological tragedies of Chernobyl or the Aral Sea have a negative impact on the ecologically safe environment, which is one of the necessary elements of the "right to life" of people not only in Eastern Europe or Central Asia, but also in the entire globe. That is why President I. A. Karimov, in his speeches at the 48th, 50th, 55th sessions of the UN, proposed to solve the problem of the island at the international level and considered its negative consequences as an urgent global issue that threatens not only Uzbekistan, but the entire world community. showed International protection of the environment refers to the set of principles, norms and relations of international law that ensure the ecologically safe environment of people and the sustainable development of states